Efficacy and safety of rituximab in elderly patients with membranous nephropathy - Guo, Yanhong; Zhao, Huayan; Ren, Mingjing; Wang, Yulin; Wang, Liuwei; Tang, Lin (Frontiers in Pharmacology, 2023)
Objectives: Advancing age is a risk factor for treatment-related side effects and mortality in membranous nephropathy (MN) patients treated with traditional immunosuppressive regimens. This study aimed to determine the efficacy and safety of rituximab (RTX) in the treatment of elderly patients with MN. Methods: We performed a single center retrospective review of 37 consecutive MN patients aged 70 and older at the time of RTX infusion. We also enrolled 76 young patients (<70 years old) with MN as the control group. We assessed clinical and laboratory indices, remission rates, and adverse events at RTX infusion, 3 months, and last visit. Results: A total of 37 elderly patients with MN were included, with a median follow-up period of 15.50 (10.00, 24.40) months. Of the 37 patients, 75.68% were male, and mean age was 71.89 ± 2.47 years. At last visit, 7 (18.92%) patients achieved complete remission, and 26 (70.27%) patients achieved complete or partial remission. There were no differences in the complete remission rate and complete or partial remission rate at last visit compared to young patients (26.32% vs. 18.92%, p = 0.387; 85.53% vs. 70.27%, p = 0.055). After RTX treatment, three of 6 elderly patients with pneumonia died due to ineffective treatment of the infection in RTX therapy courses. The results of multivariant regression analysis showed that elderly patients have an increased risk of serious infection, compared with patients younger than 70 years (OR = 32.874, 95% CI 1.300–831.490, p = 0.034). For each increase of 1 g/L in serum albumin, the risk of serious infection would decrease by 43.2% (OR = 0.568, 95% CI 0.334–0.969, p = 0.038). Conclusion: This study demonstrates that RTX is effective in the treatment of elderly patients with MN. However, we also observed a high incidence of infectious complications. Our experience was limited by its retrospective design and relatively small sample size, and further randomized controlled studies with large sample size are needed to confirm our preliminary findings.